Comprehensive care by the basic health team with a family focus on pregnant adolescents in a Peruvian health facility: A case study - Bruno-Cerro, Roberto Carlos (2024)
Introduction: Teenage pregnancy is a public health problem. According to the Ministry of Health, 8.9% of pregnancies are adolescent and are high risk due to the maternal-perinatal complications that this entails. For this reason, Peruvian regulations invoke the importance of family and community work by the "Basic Health Team". Objective: To describe the multidisciplinary work with a focus on family and community in a pregnant adolescent. Clinical case: A 14-year-old pregnant adolescent user who lived one hour away from the Contumazá Medical Post in Cajamarca, an incomplete high school student and insured with EsSalud as a beneficiary on behalf of the father. Conclusions: The pregnant adolescent received comprehensive care from the basic health team with a focus on the family and its environment, obtaining a satisfactory vaginal delivery without complications for the mother or the newborn. Therefore, it is estimated that it is feasible to reduce maternal perinatal morbidity and mortality if the work is carried out in a personalized manner with the user as a whole, educating and involving the family in the care of the pregnancy and identification of alarm signs, the participation of the "Basic Health Team" in Primary Care Establishments being transcendental.